On difference. Lack and politics in Pierre Clastres - Sebastián Barros (Íconos)
This article addresses Pierre Clastres’ analysis of what he called “societies against the State”. Its goal is to engage in a discussion of the way in which Western political theory considered the notion of difference. First, the article shows the way in which Clastres deals with the idea of lack among the peoples he studied. Instead of presenting them as societies lacking something (faith, king, law), he describes these peoples as societies against the State. Then, the article tackles Clastres’ idea of politics as the matrix for all differences. For him, politics operates on the limits of the demos, defining which differences will be legitimately articulated within the community. Finally –and briefly–, the article puts forward a way in which the analysis of contemporary political processes like Latin America populisms or the Indignants Movement in Europe could benefit from Clastres’ conception of politics and difference.